2012
DOI: 10.1021/nl2044875
|View full text |Cite
|
Sign up to set email alerts
|

Remote, Local, and Chemical Programming of Healable Multishape Memory Polymer Nanocomposites

Abstract: We show that the combination of remote, local, and chemical programming of the multishape memory effects offers unparalleled shape and function control in carbon nanotube-Nafion composites. This strategy not only allows the high-fidelity encoding and extraction of designed material shapes at different length scales (macro, micro, and nano) but also enables the reversible tunability of material functions, such as shape memorizability, mechanical properties, surface hydrophobicity, and material resealability, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 31 publications
0
80
0
Order By: Relevance
“…Nji and Li developed both a three-dimensional (3D) woven fabric reinforced SMP composite based on organic materials for impact resistance [23,24] and an SMP composite based on biomimicry. In 2012, Kohlmeyer et al described composites of SMPs and single-wall carbon nanotubes (SWCNTs) [25]. In 2013, Tridech et al developed systems to explore active stiffness control in polymer/carbon fiber nanocomposites [26].…”
Section: Smp-organic Compositesmentioning
confidence: 99%
See 2 more Smart Citations
“…Nji and Li developed both a three-dimensional (3D) woven fabric reinforced SMP composite based on organic materials for impact resistance [23,24] and an SMP composite based on biomimicry. In 2012, Kohlmeyer et al described composites of SMPs and single-wall carbon nanotubes (SWCNTs) [25]. In 2013, Tridech et al developed systems to explore active stiffness control in polymer/carbon fiber nanocomposites [26].…”
Section: Smp-organic Compositesmentioning
confidence: 99%
“…The materials were loaded with up to 9% Na-MMT. By dynamic mechanical thermal analysis (DMTA), the glassy (elastic) modulus in bending at 25 C was shown to have increased from 7 GPa (neat PEMA) to above 10 GPA (9% loaded composite) and the rubbery modulus was reported to have increased from about 4 MPa to above 20 MPa with the loading. The authors observed the cyclic tensile behavior of the samples and showed that the emergence of permanent strain was minimized in the neighborhood of 1-5% loading.…”
Section: Emergence Of Smpincsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these methods, photothermal activation is a general approach that requires the dispersion of appropriate light absorbers in the polymer, capable of converting photons into heat. Different types of absorbers can be employed such as inks and organic dyes [16,17], gold nanoparticles or nanorods [18][19][20][21][22][23], graphene [24][25][26], carbon nanotubes [27], and metal complexes [28,29]. The excitation wavelength depends on the absorber type and can vary from the near IR, the visible or the UV range.…”
Section: Introductionmentioning
confidence: 99%
“…These materials can be obtained by dispersing Au nanoparticles (NPs) in the epoxy matrix. Due to the high extinction coefficient of Au NPs [33], photothermal activation would need a very small concentration of these nanoparticles [27]. In turn, this assures good transparency and improved light penetration.…”
Section: Introductionmentioning
confidence: 99%